Meningkatkan Hasil Belajar Matematika Materi Operasi Hitung Bilangan Bulat Dengan Menggunakan Pendekatan Kontektual - Muhamad Akrom; Afir Dwi Kurniawati (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
The background of this study is the low mathematics learning outcomes of integer arithmetic operations material in grade IV students of SD Negeri 1 Manjung. This study aims to improve mathematics learning outcomes of integer arithmetic operations material using a contextual approach. This research is a Classroom Action Research (CAR) with two cycles. The subjects of the study were all grade IV students of SD Negeri 1 Manjung in the 2024/2025 academic year totaling 16 students. Data collection techniques include observation, essay test questions, documentation. Based on the classroom action research that has been carried out, it was found that the contextual approach can improve the mathematics learning outcomes of grade IV students of SD Negeri 1 Manjung. This can be seen from the initial conditions of mathematics learning outcomes that the number of students who achieved KKM was 37.5% with an average score of 61.25 increasing to 56.25% with an average score of 68.13 in cycle I and reaching 75% with an average score of 74.38 in cycle II. Based on the results of the study, it can be concluded that implementing a contextual approach can improve the learning outcomes of mathematics on the material of integer arithmetic operations for grade IV students of SD Negeri 1 Manjung in the 2024/2025 academic year